Assessing the liquefaction potential of seabed soils based on ocean ambient noise in the Yellow River Delta - Li, Yang; Meng, Qingsheng; Wang, Shilin; Wang, Wenjing; Chen, Yuhong (Frontiers in Marine Science, 2023)
Seabed soils can undergo liquefaction under cyclic loading, resulting in a rapid decrease in strength and stiffness, which may lead to the destruction of offshore structures. Therefore, the assessment of seabed soil liquefaction will become an important factor in disaster prevention and risk analysis in coastal and offshore engineering construction. In this study, the ocean ambient noise with low-frequency, long-wavelength, and wide-band characteristics was used to conduct and analysis noise based on the horizontal-to-vertical spectral ratio method. The shear wave velocity of the seabed soil was obtained by inverting the ocean ambient noise dataset. Then, we proposed a shear wave velocity threshold that can be used for liquefaction assessment of Holocene unconsolidated fine-grained soils by statistical analysis, and the liquefaction potential of the soils was evaluated according to 1-D shear wave velocity structures and 2-D shear wave velocity profiles. The results showed that the distribution of the shear wave velocity obtained by inverting ocean ambient noise was generally consistent with the measured shear wave velocity in the field, indicating that the inversion results have a certain degree of accuracy. A shear wave velocity threshold of 200 m/s was proposed for liquefaction assessment, determining that the soils within 0-10 m depth in the coastal area of Yellow River Delta have liquefaction potential. This result is in accordance with the assessment based on the critical shear wave velocity, indicating that this threshold is applicable to the assessment of seabed soil liquefaction in the Yellow River Delta. The in-situ observations of ocean ambient noise provide a more convenient, economical, and environmentally friendly method, which can help to investigate marine geology disasters and serve marine engineering construction.